How to work with visual artists to move developmental and life-course criminology forward - Harris, David John (Frontiers in developmental and life-course criminology, 2024)
Information graphics and data visualisation have become common and increasingly prominent in many communication and information environments including education, journalism, social media, and academic research and publishing. However, there has been comparatively little progress in the actual development of data visualisation among criminologists specifically. Data visualisation is a step outside traditional criminology's comfort zone, where there is a heavy reliance on cross-sectional sampling methods and spreadsheet-based statistics. These data sources do not easily lend themselves to longitudinal analysis and certainly not to answering qualitative questions. In this chapter we explore and reflect on case studies of our collaboration between a criminologist and designer/communicator in data visualisation, which occurred partly as a response to Maltz's (1998) appeal for the field to consider the benefits of representing criminological elements in graphical ways. In our reflection, we place particular emphasis on how the process of collaboration led not only to visualisation outcomes but to new ways of examining and understanding criminological data in the context of developmental and life-course criminology (DLC). We consider what we learn from creative arts approaches to problem-solving and the additional opportunities that can arise when criminologists and creative artists collaborate.